Regulasi Emosi Pada Pasien Rumah Singgah Gajah Mada - Kusnul Khotimah; Sri Ernawati (Pusat Riset dan Inovasi Nasional, 2024)
Emotion regulation refers to an individual's ability to control their emotions. Everyone regulates their emotions to manage their life. In reality, a variety of factors can interfere with emotion regulation skills. The single most important factor that can influence the emotion regulation process is the level of self-control that each individual has. For this reason, patients need to have strong emotional regulation abilities. Emotion regulation Emotional balance is a person's ability to assess, cope with, manage and express emotions appropriately. In this research the method is to explain and discuss. The subjects or informants in this discussion are Shelter Home Patients. The results of this study show that halfway house patients have emotional regulation skills where each subject has the ability to control and regulate their emotions which appear at an appropriate level of intensity. Data collection using in-depth interview techniques and observation. Before the interview process, the researcher provided an overview of emotional regulation and the aims of the research. Participants in this study involved 7 patients at the Gajah Mada shelter in Surakarta City.